2021
DOI: 10.3389/fimmu.2020.612706
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Variable Pharmacokinetic Profile of Eculizumab in an aHUS Patient

Abstract: BackgroundWith the introduction of eculizumab, a C5-inhibitor, morbidity and mortality improved significantly for patients with atypical hemolytic uremic syndrome (aHUS). In view of the high costs, actual needs of the drug, and increasing evidence in literature, aHUS patients can be treated according to a restrictive eculizumab regimen. We retrospectively analyzed the pharmacokinetic and dynamic parameters of eculizumab in one patient in time, emphasizing various factors which could be taken into account durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…We showed a pronounced effect of proteinuria on the pharmacokinetics of eculizumab in patients with aHUS. It has been demonstrated that severe proteinuria at (or shortly after) aHUS onset is very common, 17,18 underlining the relevance of our findings. In our aHUS population, severe proteinuria was mainly seen at diagnosis but can also occur during treatment over time.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We showed a pronounced effect of proteinuria on the pharmacokinetics of eculizumab in patients with aHUS. It has been demonstrated that severe proteinuria at (or shortly after) aHUS onset is very common, 17,18 underlining the relevance of our findings. In our aHUS population, severe proteinuria was mainly seen at diagnosis but can also occur during treatment over time.…”
Section: Discussionsupporting
confidence: 75%
“…10 Previous studies showed that several monoclonal antibodies, including eculizumab, can be detected in urine of patients with severe proteinuria. [11][12][13][14] In addition, proteinuria was associated with increased clearance of various monoclonal antibodies, 13,[15][16][17] but the effect of different degrees of proteinuria on the exposure to eculizumab has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] reported faster eculizumab clearance when patients had higher sC5b-9 concentrations. We recently showed a case of increased eculizumab clearance that was probably due to increased proteinuria, a condition that is not uncommon in aHUS patients [ 33 ]. Due to the high variability in PK of eculizumab, TDM is recommended to optimize therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This may also be due in part to the dose of intravenous immunoglobulin he received prior to eculizumab therapy, as it has been shown that patients receiving intravenous immunoglobulin have increased clearance of monoclonal antibodies via the neonatal Fc receptor, which results in significantly lower mean serum levels of eculizumab ( 18 ). Other factors, such as gastrointestinal bleeding and severe proteinuria, have also been suggest to affect eculizumab clearance ( 8 , 11 , 19 ). Unfortunately, one limitation of our report is that eculizumab levels, sC5b-9, and CH50 were not monitored initially in the patient's hospitalization in correlation with his worsening thrombocytopenia, though his clinical course supports that he subsequently responded to increased doses of eculizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the annual cost of maintenance therapy in a patient ≥40 kg is $576,000 for drug alone, not including intravenous access and infusion costs, patient time, and quality of life. Recently, there have been a number of reports in the literature describing various factors that affect eculizumab pharmacokinetics, including varying disease severity as well as other medical co-morbidities, further highlighting the need to individualize treatment approaches (6)(7)(8)(9). However, there remains only limited, and somewhat variable, reports in the literature to guide such approaches for patients with aHUS, For example, one published strategy for cost reduction that simply reported holding eculizumab and monitoring for relapse.…”
Section: Introductionmentioning
confidence: 99%